PENGARUH CORPORATE GOVERNANCE, MANAJEMEN LABA, UKURAN PERUSAHAAN, DAN KEPEMILIKAN KELUARGA TERHADAP TINDAKAN PAJAK AGRESIF DALAM PEMENUHAN KEWAJIBAN PERPAJAKAN (Studi Empiris Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012-2015) - Toni, Toni; Rasul, M; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to prove the effect of corporate governance, earnings management, size, and family awnership to the aggressive tax measures on manufacturing companies listed on Indonesia Stock Exchange period 2012 to 2015. Independent variables used in this study are corporate governance, earnings management, size, and family ownership. While dependent variable in this study is the aggressive tax measures. Data were analyzed using multiple regression model with help of software SPSS version 21. Sample was collected using purposive sampling method for manufacturing companies listed on the Indonesia Stock Exchange in the 2012-2015 period and obtaining a sample of 168 companies based on certain criteria. The result showed that the corporate governance and family ownership has no significant effect on aggressive tax measures. While earnings management and size has a significant effect on aggressive tax measures. It means that earnings management is due to avoid tax. Next, the bigger company shows that more aggressive in taxation policy.Keywords: Corporate Governance, Earnings Management, Size, Family Ownership, and Tax Aggressiveness